Sisterhood of Dune - Herbert, Brian (Tor, 2012)
"It is 83 years after the last of the thinking machines were destroyed in the Battle of Corrin, after Faykan Butler took the name of Corrino and established himself as the first Emperor of a new imperium. The great war hero Vorian Atreides has turned his back on politics and Salusa Secundus, flying off to parts unknown; because he was given a life-extension treatment by Agamemnon, he ages very slowly. Abulurd Harkonnen, convicted of cowardice during the Battle of Corrin, was sent away in disgrace to live on the gloomy planet Lankiveil, and his descendants continue to blame Vor for the downfall of their fortunes. Raquella Berto-Anirul has formed the Bene Gesserit School on the jungle planet Rossak as the first Reverend Mother. The descendants of Aurelius Venport and Norma Cenva have built a powerful transportation company, the Venport Spacing Fleet, using mutated, spice-saturated Navigators who fly "spacefolder ships" (precursors of Heighliners). Gilbertus Albans, the ward of the hated Erasmus, has established his own school on the bucolic planet of Lampadas where he teaches humans to become Mentats. Even so, many decades after the defeat of the thinking machines, anti-technology fervor continues to sweep across the human-settled planets, with powerful fanatical groups imposing violent purges.... "--